Women in Love - Lawrence, D. H.; Introduction and notes by Wallace, Jeff, Dr. (Ware Wordsworth Editions, 1999)
"Women in Love" was written in the years before and during World War I. Criticized for its exploration of human sexuality, the novel is filled with symbolism and poetry -- and is compulsively entertaining.The story opens with sisters Ursula and Gudrun Brangwen, characters who also appeared in "The Rainbow," discussing marriage, then walking through a haunting landscape ruined by coal mines, smoking factories, and sooty dwellings. Soon Gudrun will choose Gerald, the icily handsome mining industrialist, as her lover; Ursula will become involved with Birkin, a school inspector -- and an erotic interweaving of souls and bodies begins. One couple will find love, the other death, in Lawrence's lush, powerfully crafted fifth novel, one of his masterpieces and the work that may best convey his beliefs about sex, love, and humankind's ongoing struggle between the forces of destruction and life.
Keywords: Coal mines and mining -- England--Midlands -- Sisters